Edukasi Publik Mengenai Pasar Modal Dalam Meningkatkan Minat Berinvestasi Bagi Siswa/i MA Alwasliyah Tebing Tinggi - Sarwoto, Sarwoto; Nursaimatussadiya, Nursaimatussadiya; Sinaga, Eka Mayastika; Fitrianingsih, Fitrianingsih; Nainggolan, Benhart; Purba, David Gabriel Marudut; Siregar, Raysal Januar (STIE Bina Karya, 2025)
The community service program carried out for students of MA Alwasliyah Tebing Tinggi aims to provide an understanding of capital market investment for the younger generation, especially students, so that it can be used as provisions for students to be able to invest either through the capital market or in other forms. This introduction and understanding will focus on general investment procedures in the capital market. The role of the capital market is increasingly important for the Indonesian economy because it is one of the indicators of a country's economy. Therefore, this community service is a source of knowledge for the community, especially for students, to learn more about investment management and capital markets from an early age. Through an introduction by educating early, it is hoped that students can know what investment and capital markets are so that they understand and are interested in carrying out investment and capital market fields.